2020
DOI: 10.15562/ism.v11i2.638
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran karakteristik kanker anak di RSUP Sanglah, Bali, Indonesia periode 2008-2017

Abstract: Background: Childhood cancer is estimated to increase every year. Child cancer divided into leukemia and solid tumors. In RSCM Jakarta, the most common cancers are Acute Leukemia, Brain Tumor (10-15%), Retinoblastoma (10-12%), and other malignancies. This study aims to determine the characteristics of childhood cancer at Sanglah General Hospital Denpasar in the period 2008-2017.Method: A cross-sectional retrospective descriptive study was conducted by taking patient's medical records of leukemia and solid tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(10 reference statements)
1
1
0
1
Order By: Relevance
“…This is in accordance with data from the Indonesian Cancer Registration System (SriKanDi) for 2005-2007 which shows that the estimated incidence of cancer in children is 9 per 100,000 children with leukemia, which is the highest cancer in children (2.8 per 100,000) [2]. These results are also in line with with the results of Adinatha et al's study which showed that 58.5% of pediatric patients with cancer consisted of leukemia, where Acute Lymphoblastic Leukemia was the most common hematological malignancy found in children, covering 41% of the total, followed by other solid tumor types [9]. [11].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This is in accordance with data from the Indonesian Cancer Registration System (SriKanDi) for 2005-2007 which shows that the estimated incidence of cancer in children is 9 per 100,000 children with leukemia, which is the highest cancer in children (2.8 per 100,000) [2]. These results are also in line with with the results of Adinatha et al's study which showed that 58.5% of pediatric patients with cancer consisted of leukemia, where Acute Lymphoblastic Leukemia was the most common hematological malignancy found in children, covering 41% of the total, followed by other solid tumor types [9]. [11].…”
Section: Resultssupporting
confidence: 82%
“…In fact, cancer management is not measured based on the child's physical health alone, but also by achieving a good overall quality of life. 4 Many children who suffer from cancer can enjoy a normal life, but their health status is poor and cognitive and emotional disturbances are found [9].…”
Section: Resultsmentioning
confidence: 99%
“…Hematologoi-onkologi atau kanker darah merupakan penyakit yang ditandai dengan pertumbuhan sel yang tidak terkendali, sehingga dapat membentuk klon dan penyebaran sel-sel abnormal serta mengabaikan sinyal pengatur sel sekitarnya [8]. Sebagian penyakit hematologi-onkologi ini bermula di sum-sum tulang tempat sel darah diproduksi.…”
Section: Analisa Masalahunclassified